A method for high‐throughput production of sequence‐verified DNA libraries and strain collections. Issue 2 (13th February 2017) - Smith, Justin D; Schlecht, Ulrich; Xu, Weihong; Suresh, Sundari; Horecka, Joe; Proctor, Michael J; Aiyar, Raeka S; Bennett, Richard A O; Chu, Angela; Li, Yong Fuga; Roy, Kevin; Davis, Ronald W; et al.
Abstract: The low costs of array‐synthesized oligonucleotide libraries are empowering rapid advances in quantitative and synthetic biology. However, high synthesis error rates, uneven representation, and lack of access to individual oligonucleotides limit the true potential of these libraries. We have developed a cost‐effective method called Recombinase Directed Indexing (REDI), which involves integration of a complex library into yeast, site‐specific recombination to index library DNA, and next‐generation sequencing to identify desired clones. We used REDI to generate a library of 3, 300 DNA probes that exhibited > 96% purity and remarkable uniformity (> 95% of probes within twofold of the median abundance). Additionally, we created a collection of 9, 000 individually accessible CRISPR interference yeast strains for > 99% of genes required for either fermentative or respiratory growth, demonstrating the utility of REDI for rapid and cost‐effective creation of strain collections from oligonucleotide pools. Our approach is adaptable to any complex DNA library, and fundamentally changes how these libraries can be parsed, maintained, propagated, and characterized. Synopsis: Recombinase Directed Indexing (REDI), a new method that facilitates parsing and purification of array‐synthesized oligonucleotide pools, is presented. REDI is applied to produce a high‐quality DNA probe library and an arrayed collection of CRISPRi strains for essential yeast genes. A protocol and requisite strain resources are developed for Recombinase Directed Indexing (REDI), a method enabling parsing and purifying complex DNA libraries in yeast. The method is used to produce a highly uniform, sequence‐verified pool of ˜3, 300 oligonucleotide probes for bacterial detection. The method is also used to create an arrayed collection of ˜9, 000 CRISPR interference strains for conditional repression of yeast genes essential for fermentative or respiratory growth. Abstract : Recombinase Directed Indexing (REDI), a new method that facilitates parsing and purification of array‐synthesized oligonucleotide pools, is presented. REDI is applied to produce a high‐quality DNA probe library and an arrayed collection of CRISPRi strains for essential yeast genes.